Answer :

To Prove: cos-1 (4x3 – 3x) = 3 cos-1 x


Formula Used: cos 3A = 4 cos3 A – 3 cos A


Proof:


LHS = cos-1 (4x3 – 3x) … (1)


Let x = cos A … (2)


Substituting (2) in (1),


LHS = cos-1 (4 cos3 A – 3 cos A)


= cos-1 (cos 3A)


= 3A


From (2), A = cos-1 x,


3A = 3 cos-1 x


= RHS


Therefore, LHS = RHS


Hence proved.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove the followiMathematics - Board Papers

Solve the followiMathematics - Board Papers